The Internationalization of “West Papua” Issue and Its Impact on Indonesia’s Policy to the South Pacific Region - Floranesia Lantang; Edwin M.B Tambunan (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2020)
This research argues that the internationalization of